The overexpression of R-spondin 3 affects hair morphogenesis and hair development along with the formation and maturation of the hair follicle stem cells - Olczak, Alicja; Pieczonka, Tomasz D.; Ławicki, Szymon; Łukaszyk, Konrad; Pulawska-Czub, Anna; Cambier, Linda; Kobielak, Krzysztof (Frontiers in Physiology, 2024)
Mice hair follicles (HFs) are a valuable model for studying various aspects of hair biology, including morphogenesis, development, and regeneration due to their easily observable phenotype and genetic manipulability. The initiation and progression of hair follicle morphogenesis, as well as the hair follicle cycle, are regulated by various signaling pathways, of which the main role is played by the Wingless-type MMTV integration site family (Wnt) and the Bone Morphogenic Protein (BMP). During the hair follicle cycle, the BMP pathway maintains hair follicle stem cells (HFSCs) in a dormant state while the Wnt pathway activates them for hair growth. Given the pivotal role of the Wnt pathway in hair biology and HFSC regulation, we investigated the influence of the Wnt modulator, R-spondin 3 (Rspo3), in these processes. For this purpose, we developed a transgenic mice model with the overexpression of Rspo3 (Rspo3GOF) in the whole ectoderm and its derivatives, starting from early morphogenesis. Rspo3GOF mice exhibited a distinct phenotype with sparse hair and visible bald areas, caused by reduced proliferation and increased apoptosis of hair matrix progenitor cells, which resulted in a premature anagen-to-catagen transition with a shortened growth phase and decreased overall length of all hair types. In addition, Rspo3GOF promoted induction of auchene and awl, canonical Wnt-dependent hair type during morphogenesis, but the overall hair amount remained reduced. We also discovered a delay in the pre-bulge formation during morphogenesis and prolonged immaturity of the HFSC population in the bulge region postnatally, which further impaired proper hair regeneration throughout the mice’s lifespan. Our data supported that Rspo3 function observed in our model works in HFSCs’ formation of pre-bulge during morphogenesis via enhancing activation of the canonical Wnt pathway, whereas in contrast, in the postnatal immature bulge, activation of canonical Wnt signaling was attenuated. In vitro studies on keratinocytes revealed changes in proliferation, migration, and colony formation, highlighting the inhibitory effect of constitutive overexpression of Rspo3 on these cellular processes. Our research provides novel insights into the role of Rspo3 in the regulation of hair morphogenesis and development, along with the formation and maturation of the HFSCs, which affect hair regeneration.